EARLY DETECTION OF VILLAGE FUND FRAUD VIA FORENSIC ACCOUNTING SYSTEMS IN INDONESIA - Rizky Ridwan; Dede Riswandi; Siti Fathiyah Mashruroh; Sidik Nasir Akbar (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
The rising incidence of corruption in village funds in Indonesia poses a serious threat to rural development. Data from the Corruption Eradication Commission (KPK) for 2020–2024 show state losses exceeding IDR 2.5 trillion. This study examines the effects of forensic accounting, the village financial system (SISKEUDES), and human resource quality on the early detection of village fund fraud and tests the moderating role of moral justification. A mixed-method approach with an explanatory sequential design was employed. The quantitative phase involved 325 village officials in West Java Province and was analyzed using SEM-PLS, followed by qualitative in-depth interviews and focus group discussions to enrich interpretation. The findings indicate that forensic accounting, SISKEUDES, and human resource quality significantly improve early fraud detection. The study’s main contribution is empirical evidence that moral justification negatively moderates these relationships, weakening the effectiveness of technical systems and personnel competence. This research advances the literature by integrating technical, systemic, and psychological factors into a unified framework for village-level fraud detection, highlighting moral justification as a critical factor undermining fraud prevention.